2022
DOI: 10.3390/antibiotics11070832
|View full text |Cite
|
Sign up to set email alerts
|

Spread of Multidrug-Resistant Microorganisms

Abstract: Multidrug-resistant organisms (MDRO) are bacteria that exhibit acquired resistance to multiple antibiotics, reducing the efficacy of antimicrobial therapies [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…In recent years, the prevalence of bacterial infectious diseases and global public health emergencies due to multidrug-resistant bacteria has substantially increased. 1,2 Many studies have reported the synthesis of modern antimicrobial agents. 3,4 However, bacterial adaptation to drugs remains a challenging problem.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the prevalence of bacterial infectious diseases and global public health emergencies due to multidrug-resistant bacteria has substantially increased. 1,2 Many studies have reported the synthesis of modern antimicrobial agents. 3,4 However, bacterial adaptation to drugs remains a challenging problem.…”
Section: Introductionmentioning
confidence: 99%
“…MDROs are usually found in hospital settings where there is constant use of antibiotics. However, they are now appearing in rural and urban settings outside of healthcare facilities 47 , 48 . Colonization by MDROs does not equate to disease, but it does increase risk of infection 49 and dissemination in high EHI communities due to low SES and crowded housing 50 .…”
Section: Discussionmentioning
confidence: 99%
“…MDROs have become one of the most important threats to public health worldwide. [1] Urinary tract infections (UTIs) are the second most common infectious disease after respiratory tract infections and are one of the main types of MDRO infection. [2] UTIs occur in all ages and both genders, and involve inflammation of the urinary tract, which is characterized by a high incidence, high recurrence rate, high cost of antibiotics, and a lack of consensus on appropriate antimicrobial therapy.…”
Section: Introductionmentioning
confidence: 99%